Sinergia departamental en el gad parroquial de Ricaurte. - Villegas Arevalo, Yanira Alexandra (2022)
In the development of this case study was conducted in the Decentralized Autonomous Government of Ricaurte Parish, in which the descriptive method was applied to help obtain the maximum amount of information needed, using the interview technique that was applied to the president of the PARISH GOVERNMENT, where the result was obtained that there is a poor job performance due to the bad working environment in different departments of the entity, the main activity of the entity in question is the receipt of documents and requests made by users for the precincts, The main objective of the study is to evaluate the departmental synergy in the GAD Parroquial of Ricaurte. This information is based on the research line "Information and communication systems, entrepreneurship and innovation" and the subline "Companies and public and private institutions", since it is a governmental organization, it is immersed in the stipulated subline.